Differences in long‐term survival among liver transplant recipients and the general population: A population‐based nordic study. Issue 2 (5th January 2015) - Åberg, Fredrik; Gissler, Mika; Karlsen, Tom H.; Ericzon, Bo‐Göran; Foss, Aksel; Rasmussen, Allan; Bennet, William; Olausson, Michael; Line, Pål‐Dag; Nordin, Arno; Bergquist, Annika; Boberg, Kirsten Muri; et al.
<x xml:space="preserve">Abstract</x> Dramatic improvement in first‐year outcomes post‐liver transplantation (LT) has shifted attention to long‐term survival, where efforts are now needed to achieve improvement. Understanding the causes of premature death is a prerequisite for improving long‐term outcome. Overall and cause‐specific mortality of 3, 299 Nordic LT patients (1985‐2009) having survived 1 year post‐LT were divided by expected rates in the general population, adjusted for age, sex, calendar date, and country to yield standardized mortality ratios (SMRs). Data came from the Nordic Liver‐Transplant Registry and WHO mortality‐indicator database. Stagnant patient survival rates >1 year post‐LT were 21% lower at 10 years than expected survival for the general population. Overall SMR for death before age 75 (premature mortality) was 5.8 (95% confidence interval [CI] 5.4‐6.3), with improvement from 1985‐1999 to 2000‐2010 in hepatitis C (HCV) (SMR change 23.1‐9.2), hepatocellular carcinoma (HCC) (SMR 38.4‐18.8), and primary sclerosing cholangitis (SMR 11.0‐4.2), and deterioration in alcoholic liver disease (8.3‐24.0) and acute liver failure (ALF) (5.9‐7.6). SMRs for cancer and liver disease (recurrent or transplant‐unrelated disease) were elevated in all indications except primary biliary cirrhosis (PBC). Absolute mortality rates underestimated the elevated premature mortality from infections (SMR 22‐693) and kidney disease (SMR 13‐45) across all indications, and from suicide in HCV and ALF. SMR for cardiovascular disease was significant only in PBC and alcoholic liver disease, owing to high mortality in the general population. Transplant‐specific events caused 16% of deaths. Conclusion: standardized premature mortality provided an improved picture of long‐term post‐LT outcome, showing improvement over time in some indications, not revealed by overall absolute mortality rates. Causes with high premature mortality (infections, cancer, kidney and liver disease, and suicide) merit increased attention in clinical patient follow‐up and future research. (Hepatology 2015;61:668‐677)